2019
DOI: 10.1105/tpc.19.00150
|View full text |Cite
|
Sign up to set email alerts
|

TTL Proteins Scaffold Brassinosteroid Signaling Components at the Plasma Membrane to Optimize Signal Transduction in Arabidopsis

Abstract: Brassinosteroids (BRs) form a group of steroidal hormones essential for plant growth, development, and stress responses. BRs are perceived extracellularly by plasma membrane receptor-like kinases that activate an interconnected signal transduction cascade, leading to the transcriptional regulation of BR-responsive genes. TETRATRICOPEPTIDE THIOREDOXIN-LIKE (TTL) genes are specific for land plants, and their encoded proteins are defined by the presence of protein-protein interaction motives, that is, an intrinsi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 85 publications
5
63
0
Order By: Relevance
“…In line with the notion that scaffolding plays an important role in BR signaling, TETRATRICOPEPTIDE THIOREDOXIN-LIKE (TTL) proteins TTL1, TTL3, and TTL4 have recently been implicated in bringing BR signaling components together at the PM (Amorim-Silva et al, 2019). TTL3 forms a complex with several players in BR signaling, including BRI1, BSU1, and BZR1.…”
Section: Activation Of Br Signalingmentioning
confidence: 86%
See 1 more Smart Citation
“…In line with the notion that scaffolding plays an important role in BR signaling, TETRATRICOPEPTIDE THIOREDOXIN-LIKE (TTL) proteins TTL1, TTL3, and TTL4 have recently been implicated in bringing BR signaling components together at the PM (Amorim-Silva et al, 2019). TTL3 forms a complex with several players in BR signaling, including BRI1, BSU1, and BZR1.…”
Section: Activation Of Br Signalingmentioning
confidence: 86%
“…Together with its homologs TTL3/4, act to scaffold BR signaling components at the PM (Amorim-Silva et al, 2019) Modulators of BES1/BZR1 degradation and activation MAX2 At2g42620 At5g40140 At2g32950 At3g58040…”
Section: Kib1mentioning
confidence: 99%
“…In line with this, a recent study identified TETRATRICOPEPTIDE-REPEAT THIOREDOXIN-LIKE proteins (TTLs), which combine several protein interaction motifs, i.e. have the potential for multivalency (engaging in several simultaneous protein-protein interactions), as positive regulators of BR signalling by scaffolding BR signalling components [135]. TTL proteins become membrane-associated when BR signalling is activated and interact with BRI1, BSU1, BSK1, BIN2, and the BZR1 transcription factor, tethering many of the required signalling components in multiprotein complexes [135].…”
Section: Sub-compartmentalization and Clusteringmentioning
confidence: 76%
“…have the potential for multivalency (engaging in several simultaneous protein-protein interactions), as positive regulators of BR signalling by scaffolding BR signalling components [135]. TTL proteins become membrane-associated when BR signalling is activated and interact with BRI1, BSU1, BSK1, BIN2, and the BZR1 transcription factor, tethering many of the required signalling components in multiprotein complexes [135]. Thus, rather than as a series of isolated reactions, BR signalling might be better thought of as a signalling assembly, which could serve as a mechanism ensuring signalling specificity in light of the diverse roles that several of the signalling components engage in.…”
Section: Sub-compartmentalization and Clusteringmentioning
confidence: 99%
“…At the receptor level, the function of BRI1 can be post-translationally regulated by PUB12/13-directed ubiquitination, PP2A-mediated dephosphorylation, BKI1-mediated kinase inhibition, and BIK1-and BIR3-mediated competition for the coreceptor BAK1 [69][70][71][72][73]. At the BIN2 level, it has been reported that BIN2 is regulated by OCTOPUSor POLAR-mediated membrane sequestration, HDA6-mediated deacetylation, KIB1-mediated ubiquitination, TTL-enhanced interaction with BSU1, ABI1/2-mediated dephosphorylation, and ROS (reactive oxygen species)-mediated oxidation [74][75][76][77][78][79][80]. At the transcription level, it has been reported that PP2A phosphatases can promote BR signaling by dephosphorylating BES1 and BZR1, whereas 14-3-3 and BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) negatively regulate BR signaling by inhibiting the translocation of BES1 and BZR1 from the cytosol to the nucleus [81][82][83].…”
mentioning
confidence: 99%